Legal Implications of Trading Robots in Financial and Commodity Markets. - Arini Desita Sari; Mochammad Tanzil Multazam (Indonesian Journal of Law and Economics Review, 2024)
This study examines the legal implications of employing trading robots in both capital markets and commodity futures markets. Utilizing a normative juridical method with a statutory approach, primary and secondary legal materials are analyzed. Findings indicate that Bappebti Regulation No. 12 of 2022 currently governs the legal landscape for trading robots. Non-compliance with these regulations may invoke Article 378 of the Criminal Code, while compliant trading robots, in case of losses, may lead to civil suits under Articles 1243 and 1365 of the Civil Code. These results underscore the importance of adhering to regulatory frameworks and highlight potential legal recourse for market participants affected by trading robot activities. Highlights : Regulatory Framework: Analysis reveals the current regulatory landscape governing trading robots in capital and commodity markets, emphasizing compliance with Bappebti Regulation No. 12 of 2022. Legal Consequences: Non-compliance with regulatory standards may lead to legal repercussions under Article 378 of the Criminal Code, while adherence to regulations offers avenues for civil suits under Articles 1243 and 1365 of the Civil Code in case of losses. Implications for Market Players: The study underscores the importance for market participants to understand and adhere to legal frameworks surrounding the use of trading robots, highlighting potential consequences and avenues for recourse in both compliance and non-compliance scenarios. Keywords: Trading Robots, Legal Implications, Regulatory Compliance, Capital Markets, Commodity Futures